Modeling methods for marine science - Glover, David M.; Jenkins, William J.; Doney, Scott Christopher (Cambridge Cambridge University Press, 2011)
This is a textbook on modelling, data analysis and numerical techniques for advanced students and researchers in chemical, biological, geological and physical oceanography.
Includes bibliographical references (p. 552-563) and index.
Keywords: Marine sciences -- Mathematical models